Seabed corrosion-resistant cable and preparation method and application thereof
Through the use of modified nano -silicon nitride and other materials in the outer care layer of the submarine cable, the problem of poor corrosion resistance of submarine cables has significantly improved the corrosion resistance and service life of the cable.
Patent Information
- Application Number
- CN202411636958.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-01-28
AI Technical Summary
The outer sheath of submarine cables has poor corrosion resistance and is prone to chemical erosion in seawater, resulting in cable failure.
The external care layer materials include high-density polyethylene, polyvinyl chloride, polyurethane elastomer, modified nano-silicon nainer, stabilizer, and lubricant. Make modification to enhance the corrosion resistance of the outer guard.
It significantly improves the corrosion resistance of the outer layer of the submarine cable, slows the speed of corrosion, and prolongs the service life of the cable.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of special cables, and in particular to a corrosion-resistant cable for submarine use, a preparation method thereof and an application thereof. Background Art
[0002] With the development of economy and the increasing demand for energy resources, the development and utilization of oceans has become an important development direction. In the process of various marine activities, reliable power supply and communication guarantee are indispensable, and submarine cables are the key infrastructure for realizing these marine activities, and their importance is self-evident.
[0003] The submarine environment is extremely special and complex, which brings many severe challenges to the performance of submarine cables, especially corrosion resistance. The corrosion resistance of traditional cable outer sheath materials is poor, which makes them susceptible to chemical erosion in seawater, leading to cracking and other phenomena, thereby exposing the internal structure of the cable to seawater, causing cable short circuits and other faults. Therefore, it is urgent to develop a submarine cable with an outer sheath that has good corrosion resistance. Summary of the invention
[0004] The present invention provides a submarine corrosion-resistant cable and a preparation method and application thereof, which solves the problem of poor corrosion resistance of the outer sheath of the submarine cable in the related art.
[0005] The technical solution of the present invention is as follows: The present invention provides a corrosion-resistant cable for submarine use, comprising a conductor, the outer side of the conductor is sequentially wrapped with a metal shielding layer and an insulating layer, and the outer side of the insulating layer is provided with an outer sheath; The conductor is a copper conductor or an aluminum conductor, and the insulating layer is a cross-linked polyethylene insulating layer; The raw materials of the outer protective layer include the following components in parts by weight: 100 parts of high-density polyethylene, 20-30 parts of polyvinyl chloride, 20-30 parts of polyurethane elastomer, 30-50 parts of modified nano silicon nitride, 1-4 parts of stabilizer, and 2-5 parts of lubricant; The raw materials of the modified nano silicon nitride include acrylonitrile-butadiene-styrene copolymer and nano silicon nitride in a weight ratio of 4 to 8:100.
[0006] As a further technical solution, the metal shielding layer is aluminum foil or copper foil.
[0007] As a further technical solution, the median particle size of the nano silicon nitride is 50-100 nm.
[0008] As a further technical solution, the preparation method of the modified nano silicon nitride comprises the following steps: heating and melting acrylonitrile-butadiene-styrene copolymer, adding nano silicon nitride, dispersing evenly, and cooling to obtain the modified nano silicon nitride.
[0009] As a further technical solution, the acrylonitrile-butadiene-styrene copolymer includes a first acrylonitrile-butadiene-styrene copolymer and a second acrylonitrile-butadiene-styrene copolymer; The melt volume flow rate of the first acrylonitrile-butadiene-styrene copolymer at 220°C / 10kg is 19-34 cm 3 / 10min; The melt volume flow rate of the second acrylonitrile-butadiene-styrene copolymer at 220°C / 10kg is 5.5-9.5 cm 3 / 10min; The weight ratio of the first acrylonitrile-butadiene-styrene copolymer to the second acrylonitrile-butadiene-styrene copolymer is 1:7-3:1.
[0010] In the present invention, the use of two acrylonitrile-butadiene-styrene copolymers with different melt volume flow rates helps to further improve the corrosion resistance of the outer protective layer. It is speculated that the different melt volume flow rates of acrylonitrile-butadiene-styrene copolymers will affect the complexity of the internal structure of the outer protective layer.
[0011] As a further technical solution, the weight ratio of the first acrylonitrile-butadiene-styrene copolymer to the second acrylonitrile-butadiene-styrene copolymer is 1:1-3.
[0012] In the present invention, when the weight ratio of the first acrylonitrile-butadiene-styrene copolymer to the second acrylonitrile-butadiene-styrene copolymer is 1:1-3, it helps to further improve the corrosion resistance of the outer protective layer.
[0013] As a further technical solution, the raw material of the modified nano silicon nitride also includes 4-phenylbenzoic acid.
[0014] In the present invention, the inventors found that when the raw materials of the modified nano silicon nitride also include 4-phenylbenzoic acid, it helps to further improve the corrosion resistance of the outer protective layer. It is speculated that the addition of 4-phenylbenzoic acid can play a "bridging" role in the modified nano silicon nitride, improve the modification effect of acrylonitrile-butadiene-styrene copolymer on nano silicon nitride, thereby helping to further improve the corrosion resistance of the outer protective layer.
[0015] As a further technical solution, the weight ratio of the 4-phenylbenzoic acid to the acrylonitrile-butadiene-styrene copolymer is 1-3:8.
[0016] In the present invention, when the weight ratio of 4-phenylbenzoic acid to acrylonitrile-butadiene-styrene copolymer is 1-3:8, it helps to further improve the corrosion resistance of the outer protective layer.
[0017] As a further technical solution, the preparation method of the modified nano silicon nitride comprises the following steps: A1, dissolving 4-phenylbenzoic acid in ethanol, adding nano silicon nitride, dispersing evenly, and drying to obtain a pretreated product; A2. Melt acrylonitrile-butadiene-styrene copolymer at 210-220° C., add the pretreated material, disperse evenly, and cool to obtain the modified nano silicon nitride.
[0018] As a further technical solution, the stabilizer includes one or more of zinc stearate, dibasic lead phosphite, and dibutyltin dilaurate, preferably zinc stearate.
[0019] In the present invention, the addition of the stabilizer can ensure the stability of the raw materials during the extrusion process and ensure the overall quality of the outer protective layer.
[0020] As a further technical solution, the lubricant includes one or more of silicone masterbatch, microcrystalline wax, and stearic acid, preferably stearic acid.
[0021] In the present invention, the addition of lubricant can improve the fluidity of the raw material, prevent the melt from breaking under high shear rate, and ensure the overall quality of the outer protective layer.
[0022] The present invention also proposes a method for preparing a corrosion-resistant submarine cable, comprising the following steps: S1, blending and extruding the outer sheath raw materials to obtain an outer sheath material; S2. Wrap the metal shielding layer material and the insulating layer material around the outside of the conductor in sequence, and then extrude the outer sheath material around the outside of the insulating layer to obtain a corrosion-resistant cable.
[0023] As a further technical solution, in step S1, the temperature during extrusion is 180-220°C.
[0024] The present invention also proposes the application of the corrosion-resistant cable for submarine use or the corrosion-resistant cable prepared by the preparation method in marine development.
[0025] The working principle and beneficial effects of the present invention are: In the present invention, the outer sheath of the cable has good corrosion resistance. The corrosion-resistant nano silicon nitride particles are modified by acrylonitrile-butadiene-styrene copolymer, so that the modified nano silicon nitride can interact with the polyurethane elastomer, enhance the complexity of the internal structure of the outer sheath, greatly slow down the corrosion rate, and thus significantly improve the corrosion resistance of the outer sheath. DETAILED DESCRIPTION
[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] In the following embodiments and comparative examples, unless otherwise specified, the model of high-density polyethylene is DMDA-8008H; the model of polyvinyl chloride is SG-5; the model of polyurethane elastomer is DP 1490A; the median particle size of nano-silicon nitride is 75 nm; the conductor is a pure aluminum conductor; the metal shielding layer material is copper foil; the insulating layer material is cross-linked polyethylene, model LE0592; and the model of acrylonitrile-styrene copolymer is PN-127L200.
[0028] Example 1 A method for preparing a corrosion-resistant cable for submarine use comprises the following steps: S1. By weight, 100 parts of high-density polyethylene, 20 parts of polyvinyl chloride, 20 parts of polyurethane elastomer, 30 parts of modified nano silicon nitride, 1 part of zinc stearate and 2 parts of stearic acid are blended and extruded to obtain an outer sheath material; Among them, during extrusion, the temperature of zone 1 is 200°C, the temperature of zone 2 is 220°C, and the temperature of zone 3 is 180°C; The preparation method of modified nano silicon nitride comprises the following steps: 4 parts of acrylonitrile-butadiene-styrene copolymer (model Terluran GP-22, melt volume flow rate at 220°C / 10kg is 19cm 3 / 10min) was heated to melt at 220°C, 100 parts of nano silicon nitride was added, dispersed evenly, and cooled to obtain modified nano silicon nitride; S2. Wrap the metal shielding layer material and the insulating layer material around the outside of the conductor in sequence, and then extrude the outer sheath material around the outside of the insulating layer to obtain a corrosion-resistant cable.
[0029] Example 2 A method for preparing a corrosion-resistant cable for submarine use comprises the following steps: S1. By weight, 100 parts of high-density polyethylene, 30 parts of polyvinyl chloride, 30 parts of polyurethane elastomer, 50 parts of modified nano silicon nitride, 4 parts of zinc stearate and 5 parts of stearic acid are blended and extruded to obtain an outer sheath material; Among them, during extrusion, the temperature of zone 1 is 200°C, the temperature of zone 2 is 220°C, and the temperature of zone 3 is 180°C; The preparation method of modified nano silicon nitride comprises the following steps: 8 parts of acrylonitrile-butadiene-styrene copolymer (model Terluran GP-22, melt volume flow rate at 220°C / 10kg is 19cm 3 / 10min) was heated to melt at 220°C, 100 parts of nano silicon nitride was added, dispersed evenly, and cooled to obtain modified nano silicon nitride; S2. Wrap the metal shielding layer material and the insulating layer material around the outside of the conductor in sequence, and then extrude the outer sheath material around the outside of the insulating layer to obtain a corrosion-resistant cable.
[0030] Example 3 The difference between this embodiment and embodiment 2 is that in this embodiment, when preparing the modified nano silicon nitride, the model of acrylonitrile-butadiene-styrene copolymer is NOVODUR HH-112, and the melt volume flow rate at 220°C / 10kg is 5.5cm 3 / 10min.
[0031] Example 4 The difference between this embodiment and embodiment 2 is that, in this embodiment, when preparing the modified nano silicon nitride, the acrylonitrile-butadiene-styrene copolymer includes a first acrylonitrile-butadiene-styrene copolymer and a second acrylonitrile-butadiene-styrene copolymer in a weight ratio of 3:1; The first acrylonitrile-butadiene-styrene copolymer has a model of Terluran GP-22 and a melt volume flow rate of 19 cm / 10 kg at 220°C. 3 / 10min; The second acrylonitrile-butadiene-styrene copolymer is NOVODUR HH-112, and the melt volume flow rate at 220°C / 10kg is 5.5 cm 3 / 10min.
[0032] Example 5 The only difference between this embodiment and embodiment 4 is that, in this embodiment, the weight ratio of the first acrylonitrile-butadiene-styrene copolymer to the second acrylonitrile-butadiene-styrene copolymer is 1:7.
[0033] Example 6 The only difference between this embodiment and embodiment 4 is that, in this embodiment, the weight ratio of the first acrylonitrile-butadiene-styrene copolymer to the second acrylonitrile-butadiene-styrene copolymer is 1:1.
[0034] Example 7 The only difference between this embodiment and embodiment 4 is that, in this embodiment, the weight ratio of the first acrylonitrile-butadiene-styrene copolymer to the second acrylonitrile-butadiene-styrene copolymer is 1:3.
[0035] Example 8 The difference between this embodiment and embodiment 7 is that in this embodiment, the model of the first acrylonitrile-butadiene-styrene copolymer is Terluran GP-35, and the melt volume flow rate at 220°C / 10kg is 34cm 3 / 10min; The second acrylonitrile-butadiene-styrene copolymer is NOVODUR H802, and the melt volume flow rate at 220°C / 10kg is 9.5 cm 3 / 10min.
[0036] Example 9 The difference between this embodiment and embodiment 8 is that, in this embodiment, the preparation method of modified nano silicon nitride comprises the following steps: A1, dissolving 0.5 parts of 4-phenylbenzoic acid in 150 parts of ethanol, adding 100 parts of nano silicon nitride, dispersing evenly, and drying to obtain a pretreated product; A2, 8 parts of acrylonitrile-butadiene-styrene copolymer were melted at 220°C, added with the pretreated material, dispersed evenly, and cooled to obtain modified nano silicon nitride; The acrylonitrile-butadiene-styrene copolymer includes a first acrylonitrile-butadiene-styrene copolymer and a second acrylonitrile-butadiene-styrene copolymer in a weight ratio of 1:3; The first acrylonitrile-butadiene-styrene copolymer has a model of Terluran GP-35 and a melt volume flow rate of 34 cm at 220°C / 10 kg. 3 / 10min; The second acrylonitrile-butadiene-styrene copolymer is NOVODUR H802, and the melt volume flow rate at 220°C / 10kg is 9.5 cm 3 / 10min.
[0037] Example 10 The only difference between this embodiment and embodiment 9 is that, in this embodiment, when preparing modified nano silicon nitride, the weight portion of 4-phenylbenzoic acid is 5 parts.
[0038] Embodiment 11 The only difference between this embodiment and embodiment 9 is that in this embodiment, when preparing modified nano silicon nitride, the weight portion of 4-phenylbenzoic acid is 1 part.
[0039] Example 12 The only difference between this embodiment and embodiment 9 is that in this embodiment, when preparing modified nano silicon nitride, the weight portion of 4-phenylbenzoic acid is 3 parts.
[0040] Comparative Example 1 The only difference between this comparative example and Example 1 is that in this comparative example, the modified nano-silicon nitride is replaced by an equal amount of nano-silicon nitride.
[0041] Comparative Example 2 The only difference between this comparative example and Example 1 is that in this comparative example, the preparation method of modified nano silicon nitride comprises the following steps: heating and melting 4 parts of acrylonitrile-styrene copolymer at 220° C., adding 100 parts of nano silicon nitride, dispersing evenly, and cooling to obtain modified nano silicon nitride.
[0042] The outer sheath materials in Examples 1 to 12 and Comparative Examples 1 to 2 were subjected to the following performance tests: ① Tensile strength: refer to GB / T 1040.1-2018 "Determination of tensile properties of plastics Part 1: General" to test the tensile strength, where the test speed is 20mm / min, and the average of the results of 3 specimens in each group is taken as the final result, and the result is retained to one decimal place; ②Tensile strength retention rate: refer to GB / T 11547-2008 "Determination of resistance of plastics to liquid chemical reagents" to test the tensile strength retention rate of the outer sheath material after immersion in artificial seawater for 4 weeks. Among them, based on 1L of water, the artificial seawater contains 30g of sodium chloride, 3g of magnesium sulfate, 1g of calcium chloride and 0.7g of potassium chloride. The test temperature is 23℃. Tensile strength retention rate (%) = tensile strength after test / tensile strength before test × 100%. The average value of the results of 3 specimens in each group is taken as the final result, and the result is retained to one decimal place.
[0043] The test results are shown in Table 1 below.
[0044] Table 1 Test results of corrosion resistance of outer sheath materials
[0045] Comparison between Example 1 and Comparative Examples 1-2 shows that the corrosion resistance of the outer protective layer can be significantly improved by modifying the corrosion-resistant nano-silicon nitride particles with acrylonitrile-butadiene-styrene copolymer.
[0046] Comparison between Examples 2-3 and 4-8 shows that the use of two acrylonitrile-butadiene-styrene copolymers with different melt volume flow rates can help further improve the corrosion resistance of the outer protective layer. Comparison between Examples 4-5 and 6-7 shows that when the weight ratio of the first acrylonitrile-butadiene-styrene copolymer to the second acrylonitrile-butadiene-styrene copolymer is 1:1-3, it helps further improve the corrosion resistance of the outer protective layer.
[0047] Comparison between Example 8 and Examples 9 to 12 shows that when the raw material of the modified nano silicon nitride also includes 4-phenylbenzoic acid, it helps to further improve the corrosion resistance of the outer protective layer. Comparison between Examples 9 to 10 and Examples 11 to 12 shows that when the weight ratio of 4-phenylbenzoic acid to acrylonitrile-butadiene-styrene copolymer is 1 to 3:8, it helps to further improve the corrosion resistance of the outer protective layer.
[0048] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A corrosion-resistant cable for submarine use, characterized in that: It comprises a conductor, the outer side of which is sequentially wrapped with a metal shielding layer and an insulating layer, and the outer side of the insulating layer is provided with an outer sheath; The conductor is a copper conductor or an aluminum conductor, and the insulating layer is a cross-linked polyethylene insulating layer; The raw materials of the outer protective layer include the following components in parts by weight: 100 parts of high-density polyethylene, 20-30 parts of polyvinyl chloride, 20-30 parts of polyurethane elastomer, 30-50 parts of modified nano silicon nitride, 1-4 parts of stabilizer, and 2-5 parts of lubricant; The raw materials of the modified nano silicon nitride include acrylonitrile-butadiene-styrene copolymer and nano silicon nitride in a weight ratio of 4 to 8:
100.
2. A corrosion-resistant submarine cable according to claim 1, characterized in that: The preparation method of the modified nano silicon nitride comprises the following steps: heating and melting acrylonitrile-butadiene-styrene copolymer, adding nano silicon nitride, dispersing evenly, and cooling to obtain the modified nano silicon nitride.
3. A corrosion-resistant submarine cable according to claim 1, characterized in that: The acrylonitrile-butadiene-styrene copolymer includes a first acrylonitrile-butadiene-styrene copolymer and a second acrylonitrile-butadiene-styrene copolymer; The melt volume flow rate of the first acrylonitrile-butadiene-styrene copolymer at 220°C / 10kg is 19-34 cm 3 / 10min; The melt volume flow rate of the second acrylonitrile-butadiene-styrene copolymer at 220°C / 10kg is 5.5-9.5 cm 3 / 10min; The weight ratio of the first acrylonitrile-butadiene-styrene copolymer to the second acrylonitrile-butadiene-styrene copolymer is 1:7-3:
1.
4. A corrosion-resistant cable for submarine use according to claim 3, characterized in that: The weight ratio of the first acrylonitrile-butadiene-styrene copolymer to the second acrylonitrile-butadiene-styrene copolymer is 1:1-3.
5. The corrosion-resistant cable for submarine use according to claim 1, characterized in that: The raw materials for the modified nano silicon nitride also include 4-phenylbenzoic acid.
6. A corrosion-resistant submarine cable according to claim 5, characterized in that: The weight ratio of the 4-phenylbenzoic acid to the acrylonitrile-butadiene-styrene copolymer is 1-3:
8.
7. A corrosion-resistant submarine cable according to any one of claims 1 to 6, characterized in that: The stabilizer includes one or more of zinc stearate, dibasic lead phosphite, and dibutyltin dilaurate.
8. A corrosion-resistant submarine cable according to any one of claims 1 to 6, characterized in that: The lubricant includes one or more of silicone masterbatch, microcrystalline wax, and stearic acid.
9. The method for preparing a corrosion-resistant submarine cable according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1, blending and extruding the outer sheath raw materials to obtain an outer sheath material; S2. Wrap the metal shielding layer material and the insulating layer material around the outside of the conductor in sequence, and then extrude the outer sheath material around the outside of the insulating layer to obtain a corrosion-resistant cable.
10. Use of the corrosion-resistant cable for submarine use according to any one of claims 1 to 8 or the corrosion-resistant cable prepared by the preparation method according to claim 9 in marine development.
Citation Information
Cited By
Anti-corrosion alkali-resistant offshore wind power generation cable and preparation method thereof
CN120795452A